Application of Random Forest Classification Method in Determining the Best Quality Service in the Implementation of International Certification at ITCC ITPLN - Hendra Jatnika; Luqman Luqman; Mochamad Farid Rifai; Nasya Miranda Umar (Politeknik Piksi Ganesha Indonesia, 2025)
Information Technology Certification Center or also known as ITCC is one of the work units owned by the Institute Technology of PLN which is a unit that organizes training and international certification. In order to improve the quality of service from the activities that have been organized by ITCC, the ITCC committee always prepares a link for participants to write feedback which will later become material for evaluation by ITCC. In this study, 2,720 data were used which were divided into 2 categories, namely 1,884 data with positive sentiment categories and 836 data with negative sentiment categories. The data is processed using the Random Forest method in order to find out the optimality of knowing the method. The final result obtained from the application of the Random Forest classification method is an accuracy percentage of 88.97% with a precision value of 0.92, recall of 0.91, and f1 score of 0.92